14. Effect of Curry Leaf (Murraya koenigii) Extract to Early Spoilage of Beef - Akmal Safrijal; Razali Razali; Ismail Ismail; T. Reza Ferasyi; Nurliana Nurliana; Dian Masyitha (Jurnal Medika Veterinaria, 2017)
This study aimed to determine early spoilage of beef after addition of curry leaf extract. The sample used is beef Semimembranosus muscle which is divided into 42 parts each weight is 5 grams. This research used experimental method which consists of three treatments with two repetitions. P1 group is without curry leaf extract (control), group P2 with curry leaf extract 25% used and group P3 with curry leaf extract 50%. The entire sample is stored in a refrigerator at 4 ° C. For 7 days early spoilage test is conducted every day at 9am and 4pm. The result showed difference early spoilage time between each treatment. In P1 positive result of early spoilage time is on the 4th day and P2 positive result of early spoilage time is on the 5th day. While in P3 has not obtained positive result of early spoilage time at 7 days storage. Based on the results of this study we concluded that curry leaf extract can slow down the early spoilage time of beef